Development and pilot testing of a model to translate risk assessment data for Great Lakes Native American communities using mobile technology. Issue 1 (2nd January 2018) - Dellinger, Matthew J.; Olson, Jared; Clark, Robin; Pingatore, Noel; Ripley, Michael P.
ABSTRACT: The Chippewa Ottowa Resource Authority monitors fish contaminants in Anishinaabe (Great Lake Native American) tribal fisheries. A software program (app) was programmed to translate and operationalize these data for the first time in an interactive, personalized, and culturally tailored format. This article reports the process for creation, and preliminary community reception, of interactive fish consumption advisory using software that can be accessed via mobile phones and/or the internet. Response data to previous advisories guided the app presentation and aesthetics. The app "Gigiigoo'inaan' [Our Fish] presents personalized recommendations based on back-end calculated reference doses as well as a novel risk/benefit quantification originally presented by Ginsberg et al. (Human Ecol Risk Assess, Vol. 21, 2015, pp. 810–39) and Ginsberg and Toal (Environ Health Perspect, Vol. 117, 2009, pp. 267–75) to characterize nutritional benefits. The partnering organization, Inter-Tribal Council of Michigan recruited focus groups to pilot test the app for usability, influence on dietary behavior, and cultural appropriateness. The general concept of the app and the presentation of the data were deemed culturally acceptable and pleasing to the participants. The results suggest that risk-benefit data is valuable to end-users but meal frequency recommendations, typically based on federal guidelines, should also be clearly communicated. How these guidelines are selected and presented will likely impact the reception and adoption of consumption advice.